3D hotspot matrix of Au nanoparticles on Au island film with a spacer layer of dithiol molecules for highly sensitive surface-enhanced Raman spectroscopy - Dong-Jin Lee (Nature Portfolio, 2021)
Abstract Engineering of efficient plasmonic hotspots has been receiving great attention to enhance the sensitivity of surface-enhanced Raman scattering (SERS). In the present study, we propose a highly sensitive SERS platform based on Au nanoparticles (AuNPs) on Au island film (AuIF) with a spacer layer of 1,4-benzenedimethanethiol (BDMT). The three-dimensional (3D) hotspot matrix has been rationally designed based on the idea of employing 3D hotspots with a vertical nanogap between AuIF and AuNPs after generating large area two-dimensional hotspots of AuIF. AuNPs@BDMT@AuIF are fabricated by functionalizing BDMT on AuIF and then immobilizing AuNPs. The SERS performance is investigated with Rhodamine 6G as a probe molecule and the determined enhancement factor is 1.3 × 105. The AuNPs@BDMT@AuIF are then employed to detect thiram, which is used as a fungicide, with a detection limit of 13 nM. Our proposed platform thus shows significant potential for use in highly sensitive SERS sensors.